Advances in bi-reforming of methane: Syngas production for low-carbon energy solutions - Chan, Yi Herng; Yiin, Chung Loong; Huang, Mee Mee; Serene Lock, Sow Mun; Bridgid Chin, Lai Fui; Wee, Jia Sheng; Foong, Shin Ying; Lam, Su Shiung (Elsevier B.V., 2025)
Syngas, composed mainly of H2 and CO, is a key intermediate for the synthesis of chemicals and fuels. Traditionally, syngas is produced from steam methane reforming (SMR), a well-established but carbon-intensive process. With increasing global decarbonization efforts and high carbon footprint associated with SMR process, novel syngas production methods such as bi-reforming of methane (BRM) have gained attention. BRM, which utilizes CO2 aside from methane and steam as the feedstocks, offers significant potential for low-carbon syngas production. This review critically examines key process parameters (i.e., temperature, pressure, GHSV, feedstock composition) and their impact on BRM performance. In addition, emerging advanced techniques and reaction kinetic models of BRM are discussed comprehensively. The economic and environmental viability of BRM for syngas production are also scrutinized from various techno-economic analysis (TEA) and environmental impact assessments. This paper provides new perspectives especially on the advanced BRM techniques driven by electric/solar and presents new insights of the economic feasibility of BRM integrated with downstream processes such as chemicals production (e.g., methanol, FT fuels, dimethyl ether). A comprehensive Strengths-Weaknesses-Opportunities-Threats (S.W.O.T.) analysis is then provided, outlining the challenges and opportunities for the commercial deployment of BRM, with a particular focus on its role in achieving sustainable industrial practices. The findings and insights from this review highlight the state-of-the-art and identify the current gaps and outlook which could assist in accelerating the maturation of BRM as a feasible low-carbon syngas production route worldwide. Overall, key factors such as catalyst development, optimization of BRM reaction conditions (e.g., temperature, pressure, GHSV, feedstock composition, reactor design) and process integration (from CO2 capture, conversion to syngas, and downstream chemical synthesis) are critical for the advancement of this technology as a more holistic solution, whereas execution of carbon tax incentives/policies and premium for low-carbon products would greatly expedite the deployment of this technology.